P033 Impact of breastfeeding on Juvenile Idiopathic Arthritis outcomes. (11th November 2021) - Bettaieb, Hiba; Ben Nessib, Dorra; Maatallah, Kaouther; Ferjani, Hanene; Triki, Wafa; Kaffel, Dhia; Hamdi, Wafa
Abstract: Background: Juvenile idiopathic arthritis (JIA) is the most common, chronic rheumatic disease of childhood. The aetiology is still unclear. Over the past few years, several studies have investigated the association between JIA and environmental exposures such as infections and parental smoking. However, data concerning the influence of past breastfeeding on the presentation and the severity of JIA remain scarce and still a matter of debate (1, 2).The aim of this study was to determine the influence of breastfeeding history on the pattern and severity of JIA. Methods: A cross-sectional monocentric study was carried out on JIA patients according to International League of Associations for Rheumatology (ILAR). Demographic, clinical and biological data were collected from medical records. Breastfeeding data were obtained by interviewing mothers. Patients were divided into two groups: group 1 (G1) stands for JIA patients breastfed over 6 months and group 2 (G2) stands for JIA non-breastfed patients or patients breastfed <6 months. Data were analyzed using the SPSS statistical package. A p -value < 0.05 was considered significant. Results: Twenty-nine patients (10 male and 19 female) were enrolled. Mean age at disease onset was 9.1 ± 3.4 years [2–15]. Median diagnosis delay from symptoms onset was 3.5 ± 21. 1 SD months [1–72]. Median disease duration was 36 ± 79 SD months [7–336]. JIA subtypes were in decreasing order of frequency: enthesitisenthesitis-related arthritis ( n  = 13), oligoarticular ( n  = 8), Polyarticular RF- ( n  = 4), Polyarticular RF + ( n  = 2), systemic ( n  = 1) and psoriatic arthritis ( n  = 1). Inflammatory markers were raised in 48.3% ( n  = 14) of cases. Median ESR (raised in 41.3% of the cases) and CRP (raised in 34.4% of the cases) were 17 ± 25.1 SD mm/h [3–98] and 3 ± 18 SD mg/l [0–56]. Among patients with enthesitis-related arthritis, median BASDAI and BASFI scores were 1.8 ± 1.6 SD [0.3–6.3] and 2.5 ± 1.7 SD [0–6] respectively. Only 16 (55.2%) patients had bone densitometry. Osteoporosis and osteopenia were found in 10.3% and 13.8% of cases, respectively. Coxitis was found in 65.5% of patients ( n  = 19). Overall, 82.8% of children ( n  = 24) were breastfed. Breastfeeding was exclusive in 55.2% of cases ( n  = 16). Median breastfeeding duration was 12 ± 10.3 SD months [1.5–48]. Over two-thirds ( n  = 19) of patients were breastfed for >6 months. The statistical study revealed that G1 had significantly lesser occurrence of coxitis than G2 (57.9% vs 80%; P  = 0.032). Age at disease onset ( P  = 0.26), diagnosis delay ( P  = 0.9), raised inflammatory markers ( P  = 0.76) and the frequency of osteoporosis ( P  = 0.87) were comparable between the two groups. No correlation was noted between breastfeeding duration and the following parameters: age at disease onset, ESR rate, CRP rate, BASDAI and BASFI. Conclusions: In this study, JIA patients breastfed over 6 months had fewer coxitis occurrence. Further investigations with larger sample sizes are still required to assess the benefits of breastfeeding on JIA outcomes.